The Relationship between Imagination and Act in the Philosophy of Mulla Sadra - Sayed Mahdi Mirhadi (حکمت صدرایی, 2019)
The purpose of the present paper is to investigate the relation between the imagination or fantasy and the act, and to explain the role and the mechanism of the involvement of imagination in the field of human act. The essence of the imagination, the nature of the act and the relation between the imagination and the act, are three main questions of the present research. To explain the subject, it was used an analytical and inferential method. Preserving the forms after sensory perception of phenomena (formgiver), capturing the preserved forms (faculty of disposal) and transforming the perceptual forms (imaginal faculty, meditator) are of the main functions of the imagination in the field of cognitive and stimulating activities of the self. For Mulla Sadra, as an external object cannot be present in the soul and it is necessary to be presented a form of it (sensual and imaginary) in the soul, the reality of the act is also the same sensual form of the act, which has the ability to communicate to and unite with the soul, and the movement of the limbs and organs are merely an introduction to the creation of that form in the soul. In his view, the act can be either physical or non-physical and of course, the imagination is involved entirely and effectively in both of them, i.e. both in physical activity and in the realization of non-physical acts. Mulla Sadra considers the imagination as the source of the will to act, the origin of the inner actions of the soul, and a kind of independent act of the self.